Application of multiple residual stress determination methods to coarse-grained biomedical implant castings. Issue 10 (3rd July 2017) - Conroy, Brian; Traoré, Yéli; Paddea, Sanjooram; Kelleher, Joe; Tanner, David
ABSTRACT: ASTM F75 femoral knee implant components distort during manufacture due to residual stress re-distribution or inducement. X-ray diffraction, neutron diffraction, centre-hole drilling and the contour method residual stress determination techniques were applied to as-cast and/or shot-blasted components. The centre-hole drilling and contour methods can only be considered qualitative as a result of uncertainty associated with the elastic anisotropy of gauge volumes. Additionally, neutron diffraction experimentation returned unfeasible results. However, it was qualitatively identified that a shot-blasting shell-removal process has the ability to significantly alter the bulk residual stress state of the implants and induce a stress state which would cause distortion by re-distribution following material removal during manufacturing processes.